modulus of √3-1/√3+1  | \sqrt{3 } - 1 \div \sqrt{3} + 1 |

Question

modulus of √3-1/√3+1
 | \sqrt{3 } - 1 \div  \sqrt{3} + 1 |

in progress 0
Sarah 1 month 2021-08-18T15:03:06+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-18T15:04:41+00:00

     =  \frac{ \sqrt{3} - 1 }{ \sqrt{3}  + 1}  \\  \\  =  \frac{ \sqrt{3} - 1 }{ \sqrt{3}  + 1}  \times  \frac{ \sqrt{3} - 1 }{ \sqrt{3}   - 1}  \\  \\  =  \frac{ {( \sqrt{3}  - 1)}^{2} }{( { \sqrt{3} )}^{2} -  {1}^{2}  }  \\  \\  =  \frac{4 - 2 \sqrt{3} }{2}  \\  \\  =  2 -  \sqrt{3}

  1. Emma
    0
    2021-08-18T15:04:47+00:00

    \huge\boxed{\underline{\underline{\green{\tt Solution}}}}

     | \frac{ \sqrt{3} - 1 }{ \sqrt{3}   +  1} |

     =  \frac{ | \sqrt{3}  - 1| }{  | \sqrt{3}  + 1|  }

     =  \frac{ \sqrt{3 + 1} }{ \sqrt{3 + 1} }

     = 1

    \displaystyle\textcolor{red}{Please \:  Mark \:  it  \: Brainliest}

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )